ANALISIS KINERJA KEUANGAN PT. BANK SYARIAH INDONESIA (PERSERO) TBK PERIODE 2021-2025 - Sendy Prayogi; Muhammad Kambali (Universitas KH. Mukhtar Syafaat, 2025)
This study aims to evaluate the fundamental resilience and operational performance of Bank Syariah Indonesia (BSI) post-merger during the 2021–2025 period. The approach used is descriptive quantitative by applying horizontal trend analysis and the Risk-Based Bank Rating (RBBR) assessment system to the bank's key financial ratio components. The findings of this study indicate that this efficiency has significantly boosted profitability in 2025, as indicated by the ROA achievement of 2.65% and ROE of 18.05%. A very high CAR ratio (27.12%) triggers the opportunity cost of idle capital, while the dominance of murabahah contracts (56–60%). However, there are performance contradictions in the form of overly defensive capital management, the dominance of fixed-margin financing (murabahah), and a governance gap indicated by the stagnation of the Good Corporate Governance (GCG) rating. The implications suggest that BSI Management should immediately shift to an